Interpretive Conventions The Reader in the Study of American Fiction - Mailloux, Steven (Cornell University Press, 2018)
In Interpretive Conventions, Steven Mailloux provides a general introduction to reader-response criticism while developing his own specific reader-oriented approach to literature. He examines five influential theories of the reading process-those of Stanley Fish, Jonathan Culler, Wolfgang Iser, Norman Holland, and David Bleich. He goes on to argue the need for a more comprehensive reader-response criticism based on a consistent social model of reading. He develops such a reading model and also discusses American textual editing and literary history.